Systemic lupus erythematosus and nodular regenerative hyperplasia of the liver. Issue 2 (February 1986) - Klemp, P; Timme, A H; Sayers, G M
Abstract : A patient with systemic lupus erythematosus and nodular regenerative hyperplasia of the liver is presented.